Globalization and Urban Change : Capital, Culture, and Pacific Rim Mega-Projects - Olds, Kris 1961- (New York Oxford University Press, 2002)
"This book provides a grounded analysis of globalization and urban change in the late 20th century. Based on field work carried out in Vancouver, Hong Kong, Shanghai, Paris, and London, the author highlights the role of two transnational cultures - ethnic Chinese property developers and 'brand name' architects - in the planning and development of urban mega-projects. Case studies from Vancouver and Shanghai are used to analyse the nature of the transnational practices and networks that facilitate the production of new urban spaces on the Pacific Rim. This reflexive, situated, and interdisciplinary account offers an alternative perspective to the abstract and economistic analyses that dominate our understanding of globalization and urban change. It will be of value to human geographers, urban planners, sociologists, anthropologists, architects, economists, and political scientists; all with an interest in the processes that are reshaping the modern city."--Jacket.
Include Maps, Pictures, References and Index
Keywords: City planning -- Globalization